Values of Pancasila Ideology as a Multicultural Adhesive in Indonesia - Maswati Maswati; St. Wardah Hanafie Das (International Journal of Islamic Educational Research, 2024)
Indonesia is a country that has a diversity of cultures, religions, ethnicities, and languages. This diversity is a wealth as well as a challenge in maintaining national unity. This article discusses the role of Pancasila ideological values as a multicultural adhesive in Indonesia. Using a qualitative-descriptive method, this study shows that Pancasila values, such as social justice, just and civilized humanity, and unity, play an important role in harmonizing differences in society. This study also recommends strengthening the implementation of Pancasila values in various aspects of life to maintain social cohesion.